Acoustics characteristics of voice and vocal care in acting and other students - Varošanec-Škarić, Gordana (Array, 2008)
Based on voice history data test was used to investigate the difference between students of acting (n=45) and other students (n=45). A t-test was used to calculate the differences in acoustic parameters between two groups.